Node deployment for wireless sensor networks based on improved multi-objective evolutionary algorithm. (2017) - Wei, Kaibin
Node deployment is a crucial issue for wireless sensor networks, and it significantly affects the performance of wireless sensor networks. In this paper, we proposed a novel Node deployment algorithm for wireless sensor networks via solving the multi-objective optimisation problem. The aim of node deployment in WSN is to determine an optimal node arrangement satisfying two conditions: 1) Cover all targets in the sensing range; 2) Reduce the number of wireless sensors. The main innovation of this paper is to optimise multiple objectives, such as average energy consumption, average sensitivity area and network reliability. To solve the multi-objective optimisation problem, we improve the MOEA/D method by: 1) using the uniform design to generate aggregation coefficient vectors; 2) exploiting the simplified quadratic approximation to promote accuracy of the local search. Finally, simulation results demonstrate that the proposed algorithm outperforms other optimisation methods for all optimisation objectives.